Islamic Business Ethics In Human Resources Management - Maulana, Nurul Iman (International Journal of Sharia Business Management, 2024)
Human Resource Management (HRM) plays a pivotal role in organizational success. Incorporating Islamic business ethics into HR management is imperative in Islamic business contexts. This entails aligning business decisions with ethical principles and moral values, fostering equity, inclusivity, and sustainability. Justice, honesty, social responsibility, and employee welfare are paramount in every HR management decision. A literature review method was employed to explore Islamic business ethics in HRM. It aimed to deepen understanding and critically analyze the application of Islamic ethical principles in HRM practices. Islamic business ethics provide a robust framework for ethical and responsible HRM, emphasizing justice, transparency, and employee development. By integrating these principles, businesses can grow ethically and responsibly, considering employee welfare and achieving business goals.